A field study of factors and variables regarding tour destination loyalty of Cox’s Bazar in Bangladesh - Hossain, E.; Quaddus, Mohammed; Shanka, Tekle (Cognizant Communication Corporation, 2013)
It is a generally held belief that a tourism destination gets maximum benefit from loyal visitors compared to nonloyal visitors. Although literature on loyalty covers different issues, it lacks a comprehensive study of factors and variables that influence destination loyalty. Therefore, this article aims to investigate the main factors affecting destination loyalty in adopting and applying it to the world's longest beach, Cox's Bazar in Bangladesh. Initially a conceptual destination loyalty framework was developed based on the literature. An exploratory field study utilizing a deductive methodological approach was undertaken by conducting field interviews with 10 experienced visitors from multiple disciplines. Then, we utilized a content analysis based on transcription of the interviews to extract the factors and variables and further developed a loyalty framework. The outcomes of the field interviews identify three new factors (Religious Belief, Seasonal Variation, and Level of Income) that play important roles in destination loyalty judgment. In addition, nine variables (natural beauty, longest beach, reputed place, adjacent attractions, nontraditional items, time, rational price of tourism products, recommendable place, and visit again) are also found to be common and of utmost importance. The article concludes by highlighting the methodological, theoretical, managerial implications, and future research directions.